Rancang Bangun dan Analisis Antena Yagi 11 Elemen Pencatu Folded Dipole Untuk Jaringan VoIP - fandy himawan (Politeknik Negeri Malang, 2015)
The problem that often occurs in VOIP networks using wireless media is the weak signal received and transmitted by the transceiver device at a long distance from the wireless router, so that the quality of VOIP service is often disconnected. The purpose of this research is to design and realize an 11 element yagi antenna with folded feed elements. dipole as an antenna for a transceiver device whose gain is better than a built-in antenna, so that it can support VOIP services. Yagi antenna is an antenna consisting of 3 elements, namely a reflector element, a driven element and a director element. The reflector element and the director element cause the yagi antenna to be directional so that a large gain is obtained from a certain point, while the driven one is used is a folded dipole antenna which has an impedance of 300 ohms so that the matching technique to the 50 ohm transmission line becomes easier. Ghz is less than 1.5 and RL is less than -14 dB. The bandwidth obtained is 620 MHz, the gain is 16.08 dBi with directional radiation and linear polarization. In implementation, the VOIP service is stable at a distance of 50 m using a yagi antenna, compared to the less stable built-in antenna.